Videothoracoscopic splanchnicectomy as a method of treatment of the chronic pain syndromes in pancreatic cancer and chronic pancreatitis - Karolina Ziętara; Aleksander Oskroba; Natalia Pawełczak; Aleksandra Orzechowska; Mateusz Pawlina; Ilona Kowalczyk; Bartłomiej Zielonka; Cezary Stawikowski; Piotr Pawłowski; Karolina Raksa (Kazimierz Wielki University, 2023)
Background: Chronic pain is a serious problem occurring in patients suffering from pancreatic cancer or chronic pancreatitis. It often contributes to anorexia and significantly deteriorates the quality of life, including the possibility of shortening the survival of such patients. Thoracoscopic splanchnicectomy is a surgical procedure consisted of the excision of the major thoracic visceral nerve or its branches, which attend the transmission of pain stimuli from the abdominal viscera.  Aim of the study: The study aim is to indicate benefits of videothoracoscopic splanchnicectomy as a procedure performed in chronic pain management in patients suffering from pancreatic cancer and chronic pancreatitis.  Material and methods: The literature available in the databases such as PubMed, Google Scholar and polish scientific journals was reviewed, using the following keywords: videothoracoscopic splanchnicectomy, pancreatic cancer, chronic pancreatitis. Results and conclusions: Videothoracoscopic splanchnicectomy is a minimally invasive yet highly effective surgical procedure, which allows to avoid traumatizing procedures such as thoracotomy or laparotomy in patients suffering from a severe chronic pain associated with pancreatic cancer, chronic pancreatitis and other conditions. Moreover it contributes to a statistically significant decrease in pain intensity and considerably improves the quality of patients' lives.